Forage species diversity and composition, and carrying capacity of rangelands in Teluk Wondama Regency, West Papua, Indonesia - MARLYN N. LEKITOO; TEDDY LEKITOO; BUDI SANTOSO; EVI W. SARAGIH; ONESIMUS YOKU; BAMBANG TJ. HARIADI; DENY A. IYAI; LUKAS Y. SONBAIT (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Lekitoo MN, Lekitoo T, Santoso B, Saragih EW, Yoku O, Hariadi BT, Iyai DA, Sonbait LY. 2026. Forage species diversity and composition, and carrying capacity of rangelands in Teluk Wondama Regency, West Papua, Indonesia. Biodiversitas 27 (1): d270111. https://doi.org/10.13057/biodiv/d270111. Rangelands and natural pastures serve as the backbone of livestock feed. However, there is limited empirical data on their productivity and capacity to sustain livestock populations in lesser-known regions, such as Papua. The study aims to assess the botanical diversity and composition of forage in natural rangeland in Teluk Wondama Regency, West Papua, Indonesia, and to evaluate its carrying capacity. Botanical sampling was conducted by establishing 30 sample plots measuring 1×1 m2 in areas of 64 ha within the Warayaro natural rangelands. Forage productivity was estimated based on botanical composition, fresh forage, dry matter, and total digestible nutrients. The findings reveal that the rangeland in Warayaro is a heterogeneous pasture comprising 5 types of fodder, including 4 grasses and 1 legume species. Non-native species from 3 families dominated the pasture, namely Paspalum dilatatum, followed by Paspalum conjugatum, Centrosema pubescens, Eleusine indica, and Cyperus rotundus. The botanical composition consisted of 86.7% grasses and 13.3% legumes. Average forage yield is 2.0 t FM, 0.4 t ha-1 and 1.02 t ha-1 TDN. The existing Warayaro forage has a carrying capacity for cattle of 0.4 AU ha-1 yr-1 (FM), 0.3 AU ha-1 yr-1 (DM) and 0.8 AU ha-1 yr-1 (TDN). The Warayaro natural pasture has low production potential (264.7 kg TDN per 100 kg of livestock body weight) and moderate nutritional quality, with a protein content of only 11.2%. The Warayaro pasture is more suitable for growing young stock to reach a body weight of 182 kg. The carrying capacity of the rangeland for cattle and goat is 32 head yr-1 is 320 head yr-1, respectively. Key ecological recommendations include increasing the proportion of legumes through reseeding, implementing rotational grazing, and monitoring and controlling Cyperus rotundus to prevent competitive exclusion of forage species.